Distribution and health risks of organic micropollutants from home dusts in Malaysia - Yang, Jianlei; Ching, Yern Chee; Kadokami, Kiwao; Ching, Kuan Yong; Xu, Shicai; Hu, Guodong; Wang, Jihua (Chemosphere, 2022)
Indoor dust is an important medium to evaluate human exposure to emerging organic contaminants. The principal aim of this study was to determine overall status of organic micropollutants (OMPs) of indoor dust in Kuala Lumpur, Malaysia and assess their corresponding health risks. One hundred thirty-three OMPs, ascribed to 13 chemical groups, were screened by Automated Identification and Quantification System with a GC-MS database. The concentrations of OMPs ranged between 460 and 4000 μg/g, with the median concentration of 719 μg/g. The dominant chemical groups were ascribed to n-alkanes (median: 274 μg/g), plasticizers (151 μg/g), sterols (120 μg/g), and pesticides (42.6 μg/g). Cholestrol was the most abundant compound (median: 115 μg/g). Different sources and usage patterns of OMPs in various houses were expected. Toxicity values of OMPs were obtained from existing databases or predicted by quantitative structure-activity relationship models. Cumulative hazard quotients for OMPs through ingestion route were lower than one for all the dust samples, demonstrating that there was no remarkable non-cancer risk. The cancer risks of these OMPs were greater than 10−4, with cholestrol dominating 99.1% of the carcinogenic risks, which suggested that there was a significant cancer risk. This study might offer a benchmark to ensure the safety of chemical usages in future in Malaysia. [Display omitted] •Organic micropollutants of indoor dust in Kuala Lumpur were determined.•A total of 133 organic micropollutants were detected.•The distribution of organic micropollutants varied in different microenvironments.•Cumulative non-cancer risks via ingestion route were negligible.•Cumulative cancer risks from ingestion route were greater than 10−4.